Capacity Building Efforts for Rabies Diagnosis in Resource-Limited Countries in Sub-Saharan Africa: A Case Report of the Central Veterinary Laboratory in Benin (Parakou) - Djegui, Fidelia; Gourlaouen, Morgane; Coetzer, Andre; Adjin, Rachidatou; Tohozin, Rogatien; Leopardi, Stefania; Mauti, Stephanie; Akpo, Yao; Gnanvi, Corneille; Nel, Louis H.; De Benedictis, Paola (Frontiers in Veterinary Science, 2022)
Rabies has been listed as a priority zoonotic disease in many African countries and the countdown to reach the goal of eliminating dog-mediated human rabies deaths by 2030 means that disease control measures need to be applied fast. In this context, an essential pillar of any national plan to control rabies is the implementation of reliable diagnostic techniques to ensure the success of field surveillance systems. Although many African countries have received international support for the control of rabies–some countries, like Benin, have not received a similar level of support. Indeed, until 2018, Benin was not able to diagnose rabies and rabies diagnosis in animals as well as humans relied solely on observed clinical symptoms. Although the Central Veterinary Laboratory (CVL) of Parakou had the equipment to implement two recommended tests, the lack of specific reagents and skills prevented the implementation of a rabies diagnostic service. Here we present the joint efforts of the national authorities in Benin, intergovernmental agencies, and non-governmental organizations to assess the strengths and weaknesses of the government's rabies control efforts. We have applied the Stepwise Approach toward Rabies Elimination (SARE) analysis, implemented rabies diagnostic capacities at the CVL of Parakou, characterized strains of rabies virus circulating in Benin, and finally integrated an inter-laboratory comparison program.